2022
DOI: 10.5194/essd-14-865-2022
|View full text |Cite
|
Sign up to set email alerts
|

New high-resolution estimates of the permafrost thermal state and hydrothermal conditions over the Northern Hemisphere

Abstract: Abstract. Monitoring the thermal state of permafrost (TSP) is important in many environmental science and engineering applications. However, such data are generally unavailable, mainly due to the lack of ground observations and the uncertainty of traditional physical models. This study produces novel permafrost datasets for the Northern Hemisphere (NH), including predictions of the mean annual ground temperature (MAGT) at the depth of zero annual amplitude (DZAA) (approximately 3 to 25 m) and active layer thic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 78 publications
2
87
2
Order By: Relevance
“…Our results suggested that the mean ALT in the Northern Hemisphere is 81.22 ± 51.35 cm, which is similar to the previous finding that the ALT in the high latitudes was 76.95 ± 21.69 cm (Ran et al., 2021). The permafrost region of the Mongolian Plateau and Northeast China is a narrow transition zone from low to high ALT, and the average ALT variation is 232.40 ± 47.95 cm.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggested that the mean ALT in the Northern Hemisphere is 81.22 ± 51.35 cm, which is similar to the previous finding that the ALT in the high latitudes was 76.95 ± 21.69 cm (Ran et al., 2021). The permafrost region of the Mongolian Plateau and Northeast China is a narrow transition zone from low to high ALT, and the average ALT variation is 232.40 ± 47.95 cm.…”
Section: Discussionsupporting
confidence: 92%
“…This method has been used to simulate the spatial and temporal distribution of ALT in the Northern Hemisphere in 1850–2,100, with a spatial resolution of 0.5° × 0.5° (Peng et al., 2018). Recently, a statistical learning model was used to calculate the permafrost distribution and ALT in the Northern Hemisphere from 2000 to 2016 with a spatial resolution of 1 km × 1 km, while the future changes in ALT largely remains unknown (Ran et al., 2021). Although the distribution and variation of ALT in the Northern Hemisphere were modeled in previous studies (Guo & Wang, 2017; Li et al., 2022; Luo et al., 2016; Peng et al., 2018), there are gaps in our knowledge of ALT variations during the past two decades and their future changes, which is especially true for data with high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…About 30% of the increase in burned fraction after 2010 occurred in July–September, thus led to rapidly growing burned fraction in the eastern Siberia. As more consecutive permafrost exists in the eastern Siberia (Ran et al., 2021), the growing wildfires will cause long‐term ecological consequences including permafrost degradation and carbon emission (Munkhjargal et al., 2020; Ponomarev et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, covered by larger area of consecutive permafrost, the eastern Siberia is more likely to be ignited than the western Siberia under the increasing lighting strikes conditions caused by warming (Chen et al., 2021). Moreover, permafrost occurs mainly as the cold‐humid type in the western Siberia but as the cold‐semiarid/subhumid type in central and eastern Siberia (Ran et al., 2021). As the eastern Siberia is getting warmer and drier, these frozen soils will be more likely to burn.…”
Section: Resultsmentioning
confidence: 99%
“…This representation enables the inclusion of separate carbon pools at varying depths in the soil, and allows for an improved simulation of soil carbon stocks (Koven et al, 2013). This is of particular importance in the northern latitudes, where carbon stocks are expected to exist at much greater depths than the 1m considered in this study (Tarnocai et al, 2009;Ran et al, 2021). This can be seen in Table 3, where increased magnitudes of soil carbon stocks are shown when increased depths are considered using the empirical datasets.…”
Section: (A)mentioning
confidence: 95%